Nonlinear analysis of race walking gait: movement variability, entropy and motor skills assessment - Preatoni, E.; Rodano, R. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The aim of this study was to explore the issue of motor skills characterisation, by assessing the regularity of motor patterns during race walking gait. Seven competitive race walkers` action was analysed through an optoelectronic system and a force platform. Sample entropy, a nonlinear dynamics tool, was adopted to evaluate the regularity of a selection of kinematic and kinetic variables. Results allowed to characterise athletic skill and to evidence the changes that may occur over time. In particular, the subtle anomalies of an injured subject were detected. Sample entropy appeared a valid means for individual monitoring in sports and gave clues for possible injury prevention.